A dual photoredox-nickel strategy for remote functionalization via iminyl radicals: radical ring-opening-arylation, -vinylation and -alkylation cascades - Dauncey, Elizabeth M. (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
A divergent strategy for the remote arylation, vinylation and alkylation of nitriles is described. These processes proceed through the photoredox generation of a cyclic iminyl radical and its following ring-opening reaction. The distal nitrile radical is then engaged in nickel-based catalytic cycles to form C–C bonds with aryl bromides, alkynes and alkyl bromides.